Echoes of old age: Reflections on the union between educability and a full life in community - Díaz San Juan, Rodrigo Alejandro; Curilén Manque, Javiera Soledad; Rojas Curin, Génesis Fernanda (PEM. Revista de Didáctica, Evaluación e Innovación, 2025)
Reflecting on mental health in old age in Chile implies recognizing the rapid population aging and the emotional challengesfaced by many older adults, especially in rural contexts. With the purpose of understanding how they live and what factors they consider protective of their well-being, this research was developed using a qualitative phenomenological–hermeneutic approach, through semi-structured interviews conducted with six participants from the Perquenco Day Center.The analysis of their accounts allowed for the identification of four main categories linked to well-being: fulfillment, the hu-man person, integral well-being, and experiences of risk. The participants’ voices revealed that their mental health is a dyna-mic construction sustained by practices of self-care, social support, spirituality, and a sense of purpose. Despite experiences of loneliness, physical deterioration, and fear of dependency, resilient strategies emerge that reflect a profound capacity foradaptation.The discussion revealed strong connections with theoretical models such as the biopsychosocial approach and logotherapy, highlighting the importance of purpose and meaningful bonds. However, an important question arises for the researchers: Is the development of all these potentialities possible thanks to an education that connects the person’s life in advance,without waiting until the final stage of life? Likewise, what will future generations of older adults be like—those who grow up in a society marked by competition and post-truth?In conclusion, it is possible to observe how the wisdom of older adults can, to some extent, prompt a rethinking of today’s societal course, and how formal education may be reproducing a society lacking humanization.
Keywords: Well-being; Older adults; Educability; Education; Wisdom; And purpose